Bosnia and Herzegovina : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper provides background information for the 1998 Article IV Consultation with Bosnia and Herzegovina. The paper contains an overview of economic and political developments. It describes the establishment of the Central Bank of Bosnia and Herzegovina, developments in the financial sector, and external sector developments and policies. The paper highlights that in formulating their economic program for 1998-99, the authorities in all regions indicated their commitment to an economic strategy based on the maintenance of cautious macroeconomic policies, the rebuilding of public administration, market-oriented structural reforms, and a well-coordinated reconstruction program.